Evaluation of Four Types of Kilns Used to Produce Charcoal from Several Tree Species in Mexico - Juan García-Quezada; Ricardo Musule-Lagunes; José Angel Prieto-Ruíz; Daniel José Vega-Nieva; Artemio Carrillo-Parra (Energies, 2022)
Charcoal production is an activity that dates back over the years. The objective of the study was to determine the temperature and heating ramp in industrial carbonization processes using different kiln types and to quantify its impact on yield and quality of charcoal from different firewood species. The selection of sites, kiln types, and species investigated was based on those with highest production in Mexico. Brazilian beehive kilns using Arbutus xalapensis, Quercus durifolia, and Quercus sideroxyla species were analyzed; modified Brazilian beehive kilns with Pithecellobium dulce and Tamarindus indica; Argentine half-orange kilns with Quercus magnoliifolia and Q. sideroxyla, industrial metal kilns with Brosimum alicastrum, Vitex gaumeri, Manilkara zapota, and Pouteria unilocularis. The process time, temperature, heating ramp, production yield, and quality of charcoal produced were determined. Data were analyzed in a completely random statistical design. The industrial type kilns showed the highest production yield (>35%), and the Brazilian beehive kilns obtained the longest carbonization time (>240 h). On the other hand, the modified Brazilian beehive kilns obtained the best energetic characteristics (>75% fixed carbon and <16% volatile material). A carbonization process with a slow heating ramp (<1 °C min−1) and temperatures of 500–600 °C can generate a charcoal with export quality.